Some aspects of robotization of the economy and creation of a robot manager (Journal of Economic Research & Business Administration, 2021)
Digital Kazakhstan programs are aimed at accelerating the pace of economic development of theRepublic of Kazakhstan and improving the quality of life of the population through the use of digitaltechnologies. The article is devoted to one of the most important areas of digitalization of the economy– the creation of robotic systems for managing the activities of firms, organizations and companies. Currently,robotics and robotic means are being introduced into various spheres of human activity and, inparticular, in the economy. The most effective robotization can be used in control systems of manufacturingenterprises, firms, organizations through the use of robot-managers. The article describes the functionsand tasks performed by robot managers that ensure the adaptation of firms to digital transformation,characterized by the use of broadband Internet, cloud services, RFID technologies, ERP systems, as wellas the involvement of firms and companies in e-commerce. The structure and functional characteristicsof robotic managers designed to control production processes are presented.The main structural elementsincluded in the structure of robot managers are considered. The use of robot managers to managethe activities of firms and companies will help to improve the quality of management functions, improvemanagement efficiency, which will lead to an increase in the return of investments, competitivenessand profitability of these enterprises. The robotization of our economy can become a locomotive for theoverall economic growth of Kazakhstan in the near future.Key words: economy, digitalization, management, digital technologies, robotic systems, robot managers.